Introducing hydrogen fuel cell vehicles in Malaysia - Ambrose, Angelina F.; Rasiah, Rajah; Al-Amin, Abul Quasem; Chen, Zhang (Taylor & Francis, 2018)
This paper attempts to evaluate potential reductions in climate damage following the introduction of hydrogen fuel cell vehicles in Malaysia over the period 2015–2030. The simulation produced interesting results. While gross climate damage under the BAU scenario increased to RM7.1 billion in 2030, the commensurate damage under the slow, moderate and high hydrogen adaptation fell to MYR2.0 billion, MYR1.7 billion and MYR1.2 billion, respectively. CO2 emissions will fall from 214MT under the BAU scenario to 203MT, 176MT and 122MT, respectively, under the slow, moderate and high scenarios, respectively. Although real GDP is expected to stagnate over the period 2015–2030 under all three adaptation scenarios, the welfare benefits are expected to expand from the greening environment. While the high adaptation scenarios offer the best quantitative results, the choice of the intensity of adaptation will depend on the regulatory framework and the extent to which consumers can adapt.